Precise Compensation of Device Variability in IGZO-based Ferroelectric ThinFilm Transistors for Enhanced Transparent Display Performance - Joch, Daniel; Lehninger, David; Sunil, Athira; Sanctis, Shawn; Lang, Thomas; Zeltner, Johannes; Wartenberg, Philipp; Seidel, Konrad; Jank, Michael P.M. (Digest of Technical Papers - SID International Symposium, 2024)
We demonstrate the compensation of device-to-device variation in threshold voltage using programmable ferroelectric indium-gallium-zinc-oxide thin-film transistors. Furthermore, degradationinduced threshold voltage shift can be mitigated by programming, setting the characteristics back to their pristine state. This can be a promising alternative for the replacement of complex VT compensation circuits in display applications.
CRIS-Team Scopus Importer:2024-09-06
Keywords: ferroelectric; indium-gallium-zinc-oxide; OLED; programmable; thin-film transistor; threshold voltage compensation; transparent display; zirconium-doped hafnium oxide